Climate Change Impact Mitigation through Renewable Energy Use in Afghanistan - Akhunzadah, Noorahmad (Journal of Natural Sciences – Kabul University, 2020)
Afghanistan has no significant contribution to global Greenhouse Gas (GHG) emissions; however, it is deeply affected by the impacts of climate change. The primary cause of climate change and global warming is the GHG emissions resulting from the continued use of non-renewable energy resources such as fossil fuels (coal, petroleum, and natural gas). On the other hand, renewable energy resources (e.g., hydropower, solar, wind, hydrothermal, biomass) serve as alternatives to non-renewable energy sources and are essential means of mitigating and adapting to climate change. Renewable energy sources, including hydropower, solar, wind power, and biomass, are abundant, and their capacity far exceeds the total national electricity demand. With vast electricity potential, abundant water resources, and extensive arable land, Afghanistan has significant capacity to adapt to and mitigate the impacts of climate change. Therefore, the main objective of this paper is to assess the country's renewable energy resources and their role in climate change mitigation and sustainable development.